2006
DOI: 10.1098/rsbl.2006.0514
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive divergence of scaling relationships mediates the arms race between a weevil and its host plant

Abstract: Coevolution of exaggerated morphologies between insects and plants is a well-known but poorly understood phenomenon in evolutionary biology. In the antagonistic interaction between a seed-predatory insect, the camellia weevil (Curculio camelliae), and its host plant, Japanese camellia (Camellia japonica), we examined the evolutionary trajectory of an exaggerated offensive trait of the weevil (rostrum length) in terms of scaling relationship. Sampling throughout Japan revealed that the ratio of the rostrum leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 24 publications
4
85
0
Order By: Relevance
“…At the whole‐eye level, changes in static allometric scaling relationships are restricted to grade shifts, with slope shifts entirely absent. This supports previous claims based on comparisons among closely related species or artificial selection experiments that allometric scaling relationships can evolve but that grade shifts are easier to achieve than slope shifts (Bolstad et al., 2015; Emlen & Nijhout, 2000; Frankino et al., 2005, 2007; Pélabon et al., 2014; Tobler & Nijhout, 2010; Toju & Sota, 2006; Voje et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…At the whole‐eye level, changes in static allometric scaling relationships are restricted to grade shifts, with slope shifts entirely absent. This supports previous claims based on comparisons among closely related species or artificial selection experiments that allometric scaling relationships can evolve but that grade shifts are easier to achieve than slope shifts (Bolstad et al., 2015; Emlen & Nijhout, 2000; Frankino et al., 2005, 2007; Pélabon et al., 2014; Tobler & Nijhout, 2010; Toju & Sota, 2006; Voje et al., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The same analysis was used to compare head capsule width between the larvae of both species. To detect any interspecific difference in the scaling relationship between adult rostrum length and body size, we compared females of both species, adapting the methodology used by Toju and Sota (2006a) for intraspecific population analyses. We carried out these analyses only on females, as their rostrums are longer, used for drilling oviposition holes, and thus susceptible to a stronger selection pressure.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In beetles, high species richness is frequently associated with phytophagy and diversity of host plants (Farrell and Mitter 1998;Kergoat et al 2005;Hunt et al 2007). Host plantherbivore interactions may result in differences in allometric shape or in body size in response to specialized feeding, which may lead to species diversification (e.g., Farrell and Mitter 1998;Kergoat et al 2005;Toju and Sota 2006a; see Strauss and Zangerl 2002 for a review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the genus Curculio, it has been shown that the imbalance between the length of the rostrum and the thickness of the host fruit wall determine the strength of local selection (Toju & Sota, 2006a), which in a long term evolution would have contributed to the increase of species diversity. The huge polymorphism of Curculio, especially in relation to rostrum length, provides an unambiguous example of adaptive radiation Toju & Sota, 2006b), for which two major routes have been pointed out: the Afrotropical species of Curculio are believed to have radiated on tropical fig trees while a second lineage radiated on temperate Fagales (Perrin, 1992). The African fig feeding species of Curculio are suggested to be a sister group of all seed feeding species .…”
Section: Introductionmentioning
confidence: 99%